Bio-economic analysis of ESBN fishery of Kumira, the coastal area of Chittagong, Bangladesh - Mondal, Md Atiqul Islam; Kader, MA; Nabi, Md Rashed Un; Siddiqui, Abdullah Al Mamun; Billah, Md Masum; Asif, Abdulla Al (Asian Journal of Medical and Biological Research, 2018)
The present investigation was conducted from May to December 2005 at Kumira, the representative area of Chittagong coast for bio-socioeconomic analysis of ESBN fishery. In catch composition of Kumira, it was observed that finfish occupied 77.03 %, shrimp 19.82 % and crab 3.15 % and the average catch per boat per day were found 16.6 kg in Kumira. The highest total catch per boat per day (50 kg) was found in October at Kumira. The lowest catch was found (2 kg) in August at Kumira. The average total catch per landing center per month was found 14805 kg at Kumira. The average catch per fishermen per day was found 3.39 kg at Kumira and the average cost per boat per month was about 7,813 Tk in the study area. Average sale per month was found over 18,713 Tk in Kumira. During the month July and August most of the fishermen were engaged in Hilsa fishing with the Hilsa gill net resulting the total catch was with ESBN lowest in those months. Asian J. Med. Biol. Res. September 2018, 4(3): 315-322